First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Dynamics and Eco‐Genomics of Baltic Sea Nitrifiers: Seasonality, Niches, Interactions and Genomic Uniqueness - Sukki Sookyoung Kim; Elisa D'Agostino; David M. Needham (Environmental Microbiology, 2026)
Nitrification is widespread across marine systems, yet the ecological and evolutionary drivers shaping nitrifier populations remain largely unknown. The Baltic Sea, a brackish basin with pronounced gradients in salinity, oxygen, nutrients and strong seasonality, is a valuable model environment to investigate these questions. Here, we combined metagenomics and rRNA gene sequencing to characterise the spatiotemporal dynamics and genomic diversity of nitrifiers, alongside physicochemical measurements. Nitrifiers were persistently abundant throughout aphotic waters, with vertical niche partitioning and seasonal peaks in surface waters from late fall to early spring. The seasonal peaks were positively correlated with nitrite, nitrate and diverse other prokaryotes, and negatively correlated with solar radiation and chlorophyll. To probe the genomic basis of these ecological patterns of the numerically dominant nitrifier, we recovered five novel genomes of ammonia‐oxidising archaea through metagenomics of bulk samples and selective enrichments, including the dominant taxon from aphotic depths. Comparative genomics showed high gene conservation, with variation largely in genes linked to interactions with the external environment and nitrogen and phosphorus metabolism between central surface and deep types. Together, our study provides insights into niches of Baltic Sea nitrifiers and begins the process of understanding the mechanisms and functional implications of these patterns.

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Environmental drivers of Atrina zelandica habitat suitability in Tauranga Harbour - Brooke G. Ellis‐Smith; Hazel R. Needham; Fabrice Stephenson; Jenny R. Hillman; Andrew M. Lohrer; Joanne I. Ellis; Conrad A. Pilditch (New Zealand Journal of Marine and Freshwater Research, 2025)
Fan shells (Family Pinnidae) have high ecological importance but are facing global declines including in New Zealand. Given the scarcity of data regarding the degree of these losses, understanding current population spatial extents and distributional drivers is needed for restoration management. A subtidal towed underwater camera survey was conducted at 62 sites to elucidate Atrina zelandica extent in Tauranga Harbour, Bay of Plenty. We observed sparse populations (occurrences at 12 sites, densities −2 ), indicating harbour‐wide declines compared to historical records. Habitat suitability modelling was used to identify possible environmental drivers influencing Atrina and predict areas suitable for restoration. The model performed well (AUC = 0.85) and predicted large areas of high habitat suitability (probability of occurrence > 0.6). Mud content (7–35%), maximum current speed ( −1 ), sediment organic matter ( −3 ) were identified as the key drivers of predicted habitat suitability. Absence of Atrina from areas of high predicted suitability and historical occupancy indicates other factors are restricting recovery. Ongoing destructive benthic activities, alongside Allee effects may be hindering natural recovery, necessitating active restoration and stressor removal to reestablish populations.

Identifying and addressing the components of extreme physical-oceanographical events for improved risk management in coastal systems - Eric P. Achterberg; Fabian Rackelmann; Ananya Ramesh; Jack O’Connor; Ovidio García-Oliva; Saranya Jayachandran; Viktoria Wichert; Xiangyu Li; Kaveh Purkiani; David M. Needham; Ingeborg Bussmann; Philipp Fischer; et al. (Frontiers in Marine Science, 2025)
Extreme physical-oceanographic events, such as marine heatwaves, fluvial floods, droughts and storm surges, have major impacts on local communities, economic sectors and ecosystems, and their frequency, intensity and duration increase due to climate change. There is a lack of understanding of the systemic drivers of extreme events as well as of their interconnected impacts on estuarine and coastal ecosystems. This knowledge is essential for assessing future impacts on ecosystem services and the local communities that depend on them, and to inform robust risk assessments and develop comprehensive risk management and adaptation strategies including early warning systems. Considering this, the German Alliance for Marine Research (DAM)-funded programme “ElbeXtreme” focuses on an integrated approach utilizing stakeholder engagement, data mining, experimental and field observations to develop novel observational and modelling approaches for assessing and monitoring risks in the Elbe estuary. The programme will deliver new insights into risks and impacts of extreme events in the estuarine system of the Elbe and the adjacent region of the North Sea (German Bight) to build a systemic risk understanding and support adaptation planning for local communities and ecosystems. Here we outline the rationale of the ElbeXtreme project and its planned activities, with the aim of stimulating national and international collaboration in tackling the urgent issue of marine and coastal risks.

Differentiation grade is highly concordant between matched primary and metastatic colorectal cancer - Camilla M. Reehorst; Jennifer K. Mooi; Charles J. Uy; Kristen A. Needham; Sarah Ellis; Ian Y. Luk; Laura J. Jenkins; Rebecca Nightingale; Fiona Chionh; Andreas Behren; Niall C. Tebbutt; David S. Williams; et al. (Clinical & Experimental Metastasis, 2025)
Differentiation grade of colorectal cancers (CRC) is histologically defined by the proportion of the tumour which retains the glandular architecture of the normal colon. Poorly differentiated CRCs display loss of glandular architecture and canonical markers of colonic differentiation and are associated with increased metastatic capacity and poorer prognosis. It is currently unclear whether poorly differentiated cells within a heterogeneous primary tumour are more likely to establish metastases and if this cellular trait is conserved in the secondary tumours, or whether metastasis is largely stochastic, with most cells in the primary tumour harboring metastatic potential. To explore this, we examined the concordance in histological grade, expression of markers of colonic differentiation, and epithelial to mesenchymal transition (EMT) in 67 matched primary and metastatic CRCs. Tumour differentiation grade was scored categorically, and expression of differentiation and EMT markers were scored as continuous variables. In matched primary-metastatic pairs, tumour grade was concordant in 88% of cases (59/67 pairs), irrespective of the site of metastasis. In tumour pairs with discordant grade (n = 8), tumour grade was higher in the metastatic lesion in 6/8 (75%) cases. Consistent with the histological concordance, expression of the key driver of colonic differentiation (CDX2); colonic lineage-specific markers (VIL1, MUC2, SYN and CHG); and the markers of epithelial-to-mesenchymal transition (E-Cadherin and Vimentin) were highly concordant between matched primary and metastatic lesions. Finally, no staining of the squamous lineage marker Cytokeratin5/6 was observed in either primary or metastatic tumours. Tumour grade assessed histologically or using expression of markers of colonic differentiation or epithelial to mesenchymal transition was largely concordant between primary and metastatic CRC. These findings complement previously reported genomic similarities between primary and metastatic lesions and demonstrate that the histological grade of a primary tumour can in most cases inform the differentiation grade of associated metastatic lesions.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Role of hepatocellular senescence in the development of hepatocellular carcinoma and the potential for therapeutic manipulation - Pramudi Wijayasiri; Stuart Astbury; Grace Needham; Philip Kaye; Mamatha Bhat; Anna M. Piccinini; Aloysious D. Aravinthan (Human Cell, 2025)
Accumulation of senescent hepatocytes is universal in chronic liver disease (CLD). This study investigates an association between hepatocyte senescence and hepatocellular carcinoma (HCC) and explores the therapeutic role of sirolimus. Background liver biopsies from 15 patients with cirrhosis and HCC and 45 patients with cirrhosis were stained for p16, a marker of cell senescence. STAM™ mice were randomized into 3 groups of 5 at 4 weeks of age and administered vehicle ± sirolimus intraperitoneally, thrice weekly, from 4 to 18 weeks of age. Placebo group was an administered vehicle, early sirolimus group was an administered vehicle with sirolimus, late sirolimus group was an administered vehicle from 4 to 12 weeks then vehicle with sirolimus from 12 to 18 weeks. The primary outcome was HCC nodule development. Senescent hepatocyte burden and senescence-associated secretory phenotype (SASP) factors were assessed in mice livers. In the human study, age (OR 1.282, 95% CI 1.086–1.513, p = 0.003) and p16 (OR 1.429, 95% CI 1.112–1.838, p = 0.005) were independently associated with HCC. In the animal study, all three groups exhibited similar MASLD activity scores ( p = 0.39) and fibrosis area ( p = 0.92). The number and the maximum diameter of HCC nodules were significantly lower in the early sirolimus group compared to placebo and late sirolimus group. The gene expression of SASP factors was similar in all groups. Protein levels of some SASP factors (TNFα, IL1β, IL-2, CXCL15) were significantly lower in sirolimus administered groups compared to placebo group. The study demonstrates an independent association between senescent hepatocyte burden and HCC. It indicates a potential chemoprophylactic role for sirolimus through SASP factor inhibition. These early results could inform a future human clinical trial. Graphical abstract

The Effect of Sediment Mud Content on Primary Production in Seagrass and Unvegetated Intertidal Flats - Georgina J. L. Flowers; Hazel R. Needham; Richard H. Bulmer; Andrew M. Lohrer; Conrad A. Pilditch (Estuaries and Coasts, 2024)
As a consequence of anthropogenic activities and climate change, accelerated terrestrial sediment runoff is causing the gradual mudification of soft sediment estuarine habitats worldwide. Increased sediment mud content (< 63 µm) has been recognised to alter seagrass morphology and cause declines in primary production in unvegetated habitats. However, the effect of increased mud content on primary production in seagrass meadows remains largely unknown. To address this, primary production in intertidal seagrass meadows ( Zostera muelleri ) and adjacent unvegetated habitats was measured in situ using benthic incubation chambers across an existing sedimentary gradient (nine sites spanning 5–33% mud content). An additional two unvegetated mudflat sites (39–49% mud content) were also sampled to expand the gradient. Seagrass net (NPP) and gross primary production (GPP) was greater than in the adjacent unvegetated habitat and did not vary with mud content, even after standardising GPP by photosynthesising biomass (i.e. photosynthetic efficiency). In contrast, in the adjacent unvegetated habitat, photosynthetic efficiency declined with increasing mud content. Inclusion of the additional mudflat sites negatively impacted NPP, GPP, and photosynthetic efficiency in the unvegetated habitat. Thus, while primary production in seagrass meadows may have some resilience to future increases in mud content (up to ~33%), further degradation and loss of seagrass habitats could result in the expansion of unvegetated habitats and ultimately lead to production losses, likely to be most acute in areas with high mud content (≥ 39%).

Controlling photodegradation in vinyl ketone polymers - M.A. Sachini N. Weerasinghe; Parker Anthony McBeth; Michelle C. Mancini; Ibrahim O. Raji; Patrick M. Needham; Kevin Yehl; Zachery Oestreicher; Dominik Konkolewicz (Chemical Engineering Journal, 2024)

Federal Food Program Participation and Beverage Intake Among Families With Low Household Income - Roya Firoozi; Heidi M. Weeks; Elizabeth Ludwig-Borcyz; Michelle Clayson; Matt Zawistowski; Belinda Needham; Katherine W. Bauer (Journal of Nutrition Education and Behavior, 2023)

Going under: The implications of sea‐level rise and reduced light availability on intertidal primary production - Georgina J. L. Flowers; Hazel R. Needham; Richard H. Bulmer; Andrew M. Lohrer; Conrad A. Pilditch (Limnology and Oceanography, 2023)
Estuarine intertidal flats are known for high rates of primary production, however, globally these ecosystems are under threat from rising sea‐level and accelerated inputs of terrestrial sediments. These stressors simultaneously alter the duration of submersion/emersion periods and water‐column turbidity impacting seafloor photoperiods. To assess how changes in submergence time and water‐clarity can affect benthic primary production, we derived in situ seasonal photosynthesis‐irradiance (P‐I) curves over 2 yr. These were conducted during submerged and emerged periods in a seagrass meadow ( Zostera muelleri ) and an unvegetated sandflat (dominated by microphytobenthos). P‐I curves showed strong light responses during submergence in both habitats and seagrass during emergence, but in the exposed sandflat there was little relationship between light availability and photosynthesis. Light‐saturated measures of gross primary production (GPP sat ) were 2.1 (submerged) and 4.1 times (emerged) higher in the seagrass than the sandflat habitat. Submerged GPP sat was always higher than emerged GPP sat , but this difference was much more pronounced in the sandflat habitat (2.4 vs. 1.3 times for seagrass). Integrating seasonally averaged P‐I curves for both tidal states into a simple model suggests that increasing submergence time could increase primary production in both habitats. However, reductions in water‐clarity will decrease submerged primary production; an effect that will be exacerbated with sea‐level rise. The sandflat trophic state was more sensitive to these environmental stressors because emerged production could not compensate for reductions during submergence. Collectively, regional management of water‐clarity may be key to providing resilience to intertidal habitats, against the inevitable effects of sea‐level rise.

Combining Techniques to Conceptualise Denitrification Hot Spots and Hot Moments in Estuaries - E. J. Douglas; J. Gammal; H. R. Needham; F. Stephenson; M. Townsend; C. A. Pilditch; A. M. Lohrer (Ecosystems, 2022)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Comprehensive single‐PCR 16S and 18S rRNA community analysis validated with mock communities, and estimation of sequencing bias against 18S - Yi‐Chun Yeh; Jesse McNichol; David M. Needham; Erin B. Fichot; Lyria Berdjeb; Jed A. Fuhrman (Environmental Microbiology, 2021)
Summary Universal primers for SSU rRNA genes allow profiling of natural communities by simultaneously amplifying templates from Bacteria, Archaea, and Eukaryota in a single PCR reaction. Despite the potential to show relative abundance for all rRNA genes, universal primers are rarely used, due to various concerns including amplicon length variation and its effect on bioinformatic pipelines. We thus developed 16S and 18S rRNA mock communities and a bioinformatic pipeline to validate this approach. Using these mocks, we show that universal primers (515Y/926R) outperformed eukaryote‐specific V4 primers in observed versus expected abundance correlations (slope = 0.88 vs. 0.67–0.79), and mock community members with single mismatches to the primer were strongly underestimated (threefold to eightfold). Using field samples, both primers yielded similar 18S beta‐diversity patterns (Mantel test, p

Kinematic and Somatosensory Gains in Infants with Cerebral Palsy After a Multi-Component Upper-Extremity Intervention: A Randomized Controlled Trial - Nathalie L. Maitre; Arnaud Jeanvoine; Paul J. Yoder; Alexandra P. Key; James C. Slaughter; Helen Carey; Amy Needham; Micah M. Murray; Jill Heathcock; Stephanie Burkhardt; Lelia Emery; Kaleigh Hague; et al. (Brain Topography, 2020)

Genome and epigenome of a novel marine Thaumarchaeota strain suggest viral infection, phosphorothioation DNA modification and multiple restriction systems - Nathan A. Ahlgren; Yangyang Chen; David M. Needham; Alma E. Parada; Rohan Sachdeva; Vickie Trinh; Ting Chen; Jed A. Fuhrman (Environmental Microbiology, 2017)
Summary Marine Thaumarchaeota are abundant ammonia‐oxidizers but have few representative laboratory‐cultured strains. We report the cultivation of Candidatus Nitrosomarinus catalina SPOT01, a novel strain that is less warm‐temperature tolerant than other cultivated Thaumarchaeota. Using metagenomic recruitment, strain SPOT01 comprises a major portion of Thaumarchaeota (4–54%) in temperate Pacific waters. Its complete 1.36 Mbp genome possesses several distinguishing features: putative phosphorothioation (PT) DNA modification genes; a region containing probable viral genes; and putative urea utilization genes. The PT modification genes and an adjacent putative restriction enzyme (RE) operon likely form a restriction modification (RM) system for defence from foreign DNA. PacBio sequencing showed >98% methylation at two motifs, and inferred PT guanine modification of 19% of possible TGCA sites. Metagenomic recruitment also reveals the putative virus region and PT modification and RE genes are present in 18–26%, 9–14% and

Every base matters: assessing small subunit rRNA primers for marine microbiomes with mock communities, time series and global field samples - Alma E. Parada; David M. Needham; Jed A. Fuhrman (Environmental Microbiology, 2016)
Summary Microbial community analysis via high‐throughput sequencing of amplified 16S rRNA genes is an essential microbiology tool. We found the popular primer pair 515F ( 515F‐C ) and 806R greatly underestimated (e.g. SAR 11) or overestimated (e.g. Gammaproteobacteria) common marine taxa. We evaluated marine samples and mock communities (containing 11 or 27 marine 16S clones), showing alternative primers 515F‐ Y (5′‐ GTG Y CAGCMGCCGCGGTAA ) and 926R (5′‐ CCGYCAATTYMTTTRAGTTT ) yield more accurate estimates of mock community abundances, produce longer amplicons that can differentiate taxa unresolvable with 515F‐C / 806R , and amplify eukaryotic 18S rRNA . Mock communities amplified with 515F‐Y / 926R yielded closer observed community composition versus expected (r 2 = 0.95) compared with 515F‐Y / 806R (r 2 ∼ 0.5). Unexpectedly, biases with 515F‐Y / 806R against SAR11 in field samples (∼4–10‐fold) were stronger than in mock communities (∼2‐fold). Correcting a mismatch to T haumarchaea in the 515F‐C increased their apparent abundance in field samples, but not as much as using 926R rather than 806R . With plankton samples rich in eukaryotic DNA (> 1 μm size fraction), 18S sequences averaged ∼17% of all sequences. A single mismatch can strongly bias amplification, but even perfectly matched primers can exhibit preferential amplification. We show that beyond in silico predictions, testing with mock communities and field samples is important in primer selection.

Modulation of Polyplex Release from Biodegradable Microparticles through Poly(ethylenimine) Modification and Varying Loading Concentration - Clark J. Needham; Sarita R. Shah; Paschalia M. Mountziaris; F. Kurtis Kasper; Antonios G. Mikos (Pharmaceutical Research, 2014)

Skier and Snowboarder Motivations and Knowledge Related to Voluntary Environmental Programs at an Alpine Ski Area - Christopher M. Little; Mark D. Needham (Environmental Management, 2011)

Context-Specific Bioturbation Mediates Changes to Ecosystem Functioning - Hazel R. Needham; Conrad A. Pilditch; Andrew M. Lohrer; Simon F. Thrush (Ecosystems, 2011)

Congruence Among Encounters, Norms, Crowding, and Management in a Marine Protected Area - Caitlin M. Bell; Mark D. Needham; Brian W. Szuster (Environmental Management, 2011)

High-Throughput Sample Preparation for the Quantitation of Acephate, Methamidophos, Omethoate, Dimethoate, Ethylenethiourea, and Propylenethiourea in Human Urine Using 96-Well–Plate Automated Extraction and High-Performance Liquid Chromatography–Tandem Mass Spectrometry - Nayana K. Jayatilaka; M. Angela Montesano; Ralph D. Whitehead; Sara J. Schloth; Larry L. Needham; Dana Boyd Barr (Archives of Environmental Contamination and Toxicology, 2011)

PLGA and PHBV Microsphere Formulations and Solid-State Characterization: Possible Implications for Local Delivery of Fusidic Acid for the Treatment and Prevention of Orthopaedic Infections - Chiming Yang; David Plackett; David Needham; Helen M. Burt (Pharmaceutical Research, 2009)

Detection of phthalate metabolites in human saliva - Manori J. Silva; John A. Reidy; Ella Samandar; Arnetra R. Herbert; Larry L. Needham; Antonia M. Calafat (Archives of Toxicology, 2005)

Glucuronidation patterns of common urinary and serum monoester phthalate metabolites - Manori J. Silva; Dana B. Barr; John A. Reidy; Kayoko Kato; Nicole A. Malek; Carolyn C. Hodge; Donald Hurtz; Antonia M. Calafat; Larry L. Needham; John W. Brock (Archives of Toxicology, 2005)

Detection of Phthalate Metabolites in Human Amniotic Fluid - M. J. Silva; J. A. Reidy; A. R. Herbert; J. L. Preau; L. L. Needham; A. M. Calafat (Bulletin of Environmental Contamination and Toxicology, 2004)

Glucuronidation patterns of common urinary and serum monoester phthalate metabolites - Manori J. Silva; Dana B. Barr; John A. Reidy; Kayoko Kato; Nicole A. Malek; Carolyn C. Hodge; Donald Hurtz; Antonia M. Calafat; Larry L. Needham; John W. Brock (Archives of Toxicology, 2003)

Phthalate Monoesters Levels in the Urine of Young Children - J. W. Brock; S. P. Caudill; M. J. Silva; L. L. Needham; E. D. Hilborn (Bulletin of Environmental Contamination and Toxicology, 2002)

GUS expression patterns from a tobacco yellow dwarf virus-based episomal vector - P. D. Needham; R. G. Atkinson; B. A. M. Morris; R. C. Gardner; A. P. Gleave (Plant Cell Reports, 1998)

Anxiolytic-like effects of PNU-101017, a partial agonist at the benzodiazepine receptor - A. H. Tang; S. R. Franklin; D. B. Carter; V. H. Sethy; L. M. Needham; E. J. Jacobsen; P. F. Von Voigtlander (Psychopharmacology, 1997)

Analytical characterization of peptide contaminants of L-tryptophan - E. R. Barnhart; V. L. Maggio; L. R. Alexander; M. C. Reilly; L. T. Gelbaum; W. E. Turner; T. K. Hine; L. L. Needham (Archives of Environmental Contamination and Toxicology, 1996)

Analytical Characterization of Peptide Contaminants of L-Tryptophan - E. R. Barnhart; V. L. Maggio; L. R. Alexander; M. C. Reilly; L. T. Gelbaum; W. E. Turner; T. K. Hine; L. L. Needham (Archives of Environmental Contamination and Toxicology, 1996)

Possible etiologic agents for toxic oil syndrome: Fatty acid esters of 3-(N-phenylamino)-1,2-propanediol - R. H. Hill; H. H. Schurz; M. Posada de la Paz; I. Abaitua Borda; R. M. Philen; E. M. Kilbourne; S. L. Head; S. L. Bailey; W. J. Driskell; J. R. Barr; L. L. Needham (Archives of Environmental Contamination and Toxicology, 1995)

Contaminants in L-Tryptophan associated with eosinophilia myalgia syndrome - Robert H. Hill; Samuel P. Caudill; Rossanne M. Philen; Sandra L. Bailey; W. Dana Flanders; William J. Driskell; Mary L. Kamb; Larry L. Needham; Eric J. Sampson (Archives of Environmental Contamination and Toxicology, 1993)

Residues of chlorinated phenols and phenoxy acid herbicides in the urine of Arkansas children - Robert H. Hill; Teresa To; James S. Holler; Douglas M. Fast; S. Jay Smith; Larry L. Needham; Suzanne Binder (Archives of Environmental Contamination and Toxicology, 1989)